Analysis of competitive activity of qualified handball players - Tyshchenko, V. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The results of competition activity of leading masculine handball commands are considered on Olympiad-2012 on the basis of estimation of efficiency of throws on a gate. Protocols of games are studied. Viewing of the videotape recordings of matches and analysis of reports of complex scientific groups which worked on Olympiad is conducted. The results of estimation of efficiency of throws of ball on a gate, executed from different positions are got. It is set that for 8 conducted games olympic champions (France), executed 363 throws on a gate (on the average 45,38 throws for a game), hammered in 229 goal (28,63 goal for a game) and attained the greatest effectiveness - 63%. It is set that efficiency of throws of handball commands is expressly up-diffused in a descending order, in obedience to busy on Olympiad places. Directions the correction of the programs of preparation of skilled handballers and control of their implementation are offered for the collapsible command of Ukraine.